Study on Flame Retardancy and Mechanism of Talc Composite Foams - Li, Xiujuan; Guo, Ruisong; Qian, Xiaodong (Frontiers in Materials, 2021)
Under high temperature, aqueous film forming foam extinguishing agent has poor flame retardancy and low fire efficiency. In order to solve this problem, talc was introduced into foam to form composite foam. The fire resistance and fire extinguishing properties of the composite foam were studied. The results showed that talc composite foam had good flame retardant resistance. when the concentration of talc reached 40 g/100 ml, the 50% liquid separation time of the composite foam was 21.1 min. The fuel burning in the anti burning tank did not ignite the gasoline in the oil pan, and burned out at 51.5 min. It was related to the structure of composite foam and the properties of talc. Due to the introduction of talc, the viscosity of the composite foam increased. The network structure of composite foam was important to the improved stability of foam. Talc powder formed a dense layer covering the oil surface, which effectively isolated the oil from the air.